2021
DOI: 10.3389/fphys.2021.685968
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Lipid Profile in Fast-Growing Broilers With Spontaneous Femoral Head Necrosis

Abstract: This study investigated lipid metabolism in broilers with spontaneous femoral head necrosis (FHN) by determining the levels of markers of the blood biochemistry and bone metabolism. The birds were divided into a normal group and FHN group according to the femoral head scores of 3-, 4-, and 5-week-old chickens with FHN, and a comparative study was conducted. The study showed that spontaneous FHN broilers had a lipid metabolism disorder, hyperlipidemia, and an accumulation of lipid droplets in the femur. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The pathology of osteomyelitis is characterized by localized inflammation, bone mineral loss, and structural damage, which share similarities with broiler BCO ( Grbic et al, 2014 ). Furthermore, a recent study on femoral necrosis pathogenicity also reported an abnormal increased in lipid metabolism and decreases in bone formation in a chicken femoral head necrosis disease model ( Fan et al, 2021 ). Therefore, by gathering all the evidence above, we proposed that oxidative stress could potentially be a co-factor involved in chicken bone necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…The pathology of osteomyelitis is characterized by localized inflammation, bone mineral loss, and structural damage, which share similarities with broiler BCO ( Grbic et al, 2014 ). Furthermore, a recent study on femoral necrosis pathogenicity also reported an abnormal increased in lipid metabolism and decreases in bone formation in a chicken femoral head necrosis disease model ( Fan et al, 2021 ). Therefore, by gathering all the evidence above, we proposed that oxidative stress could potentially be a co-factor involved in chicken bone necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…This influence on skeletal homeostasis is exerted through fatty acid oxidation in osteoblasts, the cells responsible for creating new bone and facilitating the growth and development of existing bones ( Alekos et al, 2020 ). Some studies have already reported the effect of lipid metabolism on bone growth and development in broiler chicks ( Watkins et al, 1997 ; Fan et al, 2021 ). This underscores the importance of lipid metabolism in bone health, as they may result in changes in bone homeostasis and an increase in osteopathy, such as osteoarthritis and fractures ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a bone disorder, FHN is characterized by periarticular bone disintegration and cartilage degeneration [ 22 ]. According to our previous study, FHN-affected broilers showed lipid metabolism disorders, increased lipid droplet formation, an imbalance in cartilage homeostasis, reduced extracellular matrix (ECM) formation, and simultaneous apoptosis [ 23 , 24 , 25 ]. Reduced osteogenic and chondrogenic differentiation of BMSCs in FHN-affected broilers and enhanced lipogenic differentiation were observed in the present study ( Figure 1 B).…”
Section: Discussionmentioning
confidence: 99%